Լոռի Բերդը որպես Հայաստանի պատմամշակութային առաջնակարգ հուշարձան - Դևեջյան, Սեդա; Դավթյան, Ռուբեն (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
More than half a century of excavation and research at Lori Berd necropolis has uncovered 117 tombs of local chiefs, military leaders, priests and community members. Throughout its nearly two-thousand-year history (end of the 3rd millennium BC to the 5th centuries BC), the main occupation of the people of Lori Berd has been agriculture and animal husbandry. Since the 2nd millennium BC, Lori Berd has been a powerful economic, cultural and military-political centre.
Keywords: Պատմություն; Մշակույթ